Digital Financial Literacy, Entrepreneurial Competencies and Local Government Initiatives: Keys to SMEs’ Sustainability - Ati Sumiati; Dwi Kismayanti Respati; Annisa Lutfia; Kuat Waluyo Jati (Bright Publisher, 2026)
This study examines the sustainability of Small and Medium-Sized Enterprises (SMEs’) in the Special Region of Yogyakarta, Indonesia, by assessing the combined effects of local government initiatives, digital financial literacy, and entrepreneurial competencies. The objective is to determine how these factors enhance long-term business viability in an increasingly digital economy. A mixed-method design was employed. In the qualitative phase, observations and in-depth interviews with officials from the Department of Industry and Trade explored the policy environment and SMEs’’ challenges, and themes from this stage were used to refine the survey instrument. In the quantitative phase, a structured survey of 338 SME owners measured digital financial literacy, entrepreneurial competencies, and sustainability practices. Data were analyzed using partial least squares structural equation modeling, including reliability and validity assessment, model fit evaluation, and bootstrapped hypothesis testing. Results show that both digital financial literacy (β = 0.546) and entrepreneurial competencies (β = 0.367) significantly influence SME sustainability, jointly explaining over 70% of the variance. The region’s policy environment—through initiatives such as incubation programs, Jogja Mark, the Sibakul Jogja platform, QR code payment adoption, and training—plays an enabling role in this relationship. The findings emphasize that digital financial literacy has the stronger effect, highlighting the importance of secure payment use, budgeting, and record-keeping for resilience and growth. The study contributes by integrating local policy, digital literacy, and entrepreneurial competency into a single empirical model, offering novel evidence on how these dimensions interact to support SME sustainability. The results provide actionable guidance for policymakers to strengthen digital financial capacity and tailor competency programs to sectoral needs.